(untitled) - Nishida, Kitarō (Tokyo, 1958)
Nishida has written extensively on philosophy and his complete works fill twelve volumes. The present work consists of trans lations of three of his studies that all belong to a comparatively late phase in his development. Nishida has said of himself I have always been a miner of ore; I have never managed to refine it. The absence of a last systematic refinement may indeed be felt by the reader of the present selection. Still, the reader may be impressed by the strangely new experience of life here encountered, whether his heart is moved or his mind is made to think. Nishida uses Western concepts to express his philosophical reﬂection. The reader may not always perceive this, however, since Nishida's basic experience, with Zen at its center, cannot properly be formulated in Western terms and needs the structure of a new philosophical theory. The approach to his thought is, therefore, not easy. Yet we are convinced that Nishida's philosophy can open a new way towards the mutual understanding of East and West. In the hope of contributing to this mutual comprehension, upon which a new philosophy of mankind can be erected, we venture to offer the present publication to Western readers.
Keywords: Triết học, Nhật Bản,Philosophy, Japanese